The The Effect of Realistic Mathematics Education on Ninth-Grade Students' Mathematical Problem-Solving Ability - Adam Eka Saputra; Intan Permatasari; Mega Manalu; Livi Permata; Siti Nurlaila; Siti Aisyah; Fitri Yuliana; Surdakim; Susanto; Rina Hidayati Pratiwi (Yayasan Darussalam Bengkulu, 2026)
Mathematical problem-solving ability is an essential competency that supports students' Mathematical problem-solving ability is a fundamental competency in mathematics education; however, many junior high school students still experience difficulties in solving non-routine problems. This study aimed to examine the effect of the Realistic Mathematics Education (RME) approach on ninth-grade students' mathematical problem-solving ability. A quasi-experimental study employing a nonequivalent posttest-only control group design was conducted at SMPN 10 Padang during the 2025/2026 academic year. Two intact classes were selected through cluster random sampling, comprising 32 students in the experimental group and 32 students in the control group. The experimental group received instruction using the RME approach, whereas the control group received conventional instruction. Students' mathematical problem-solving ability was measured using a five-item essay test based on Polya's four problem-solving indicators. Data were analyzed using descriptive statistics, an independent-samples t-test, and Cohen's d effect size after satisfying the assumptions of normality and homogeneity. The results showed that the experimental group achieved a higher mean score than the control group (80.75 vs. 71.19). The difference was statistically significant (t(62) = 3.46, p < .001), with a large effect size (d = 0.87). These findings indicate that the RME approach effectively improves students' mathematical problem-solving ability and supports its implementation in secondary mathematics classrooms.